University of Colorado 1969 Summer Field Season in East Baffin Island - Andrews, John T. (ARCTIC, 1970)
For the second year running, the University of Colorado's Institute of Arctic and Alpine Research (INSTAAR) and associated Departments (Biology, Geology, Geography and Anthropology) carried out a multidisciplinary research project in the region of Broughton Island, east Baffin Island (c 67°30'N). During the 1968 summer, the late glacial chronology and uplift at the head of Quajon and Narpaing fiords had been studied. An Austrian storage gauge was installed to estimate winter precipitation. Twelve individuals were involved in the 1969 summer program - this included 3 faculty members, 4 graduate students, 4 undergraduates and Mr. K. Dudley, author and teacher (Toronto). The programs were as follows: Late glacial chronology and recent crustal movements . Late glacial chronology and recent crustal movements in the Broughton Is. area . Glaciology and climatology . Archaeology . Aquatic biology . Plant ecology . Plans for the 1970 summer. The main base of operations for 1970 will be Narpaing Fiord. An intensive program will be undertaken in the glacierized and non-glacierized corrie basins, involving their heat and water balances as well as their glacial histories. Postglacial uplift and late glacial chronology of the fiord will be studied and a reconnaissance survey made of Okoa Bay and Nedlukseak Fiord. The "neoglacial" history of the mountain ice caps and glaciers lying seaward of the Penny Ice Cap will be studied and related to sea level changes.